Structural and functional insights into esterase-mediated macrolide resistance - Michał Zieliński (Nature Portfolio, 2021)
Erythromycin esterases (Eres) cleave the macrolactone ring of macrolides, a class of widely used antibiotics. Structures of EreC, in silico flexible docking studies and previous mutagenesis data lead to the proposal of a detailed catalytic mechanism for the Ere family of enzymes.